2016
DOI: 10.1021/acs.jpca.6b02990
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Investigation of Cation Proton Affinity and Proton Transfer Energy for Energetic Ionic Liquids

Abstract: Protonation of the anion in an ionic liquid plays a key role in the hypergolic reaction between ionic liquids and oxidizers such as white fuming nitric acid. To investigate the influence of the cation on the protonation reaction, the deprotonation energy of a set of cations has been calculated at the MP2 level of theory. Specifically, guanidinium, dimethyltriazanium, triethylamine, N-ethyl-N-methyl-pyrrolidinium, N-ethyl-pyridinium, 1,4-dimethyl-1,2,4-triazolium, 1-ethyl-4-methyl-1,2,4-triazolium, and 1-butyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…prepared DHB ‐ILs from chloride‐ or bromide‐ILs and Ag[BH 2 (CN) 2 ] and tested these ILs as hypergolic fluids . The proton affinity of selected anions, including the DHB anion,, and proton transfer energies from organic cations to these anions in energetic ILs were investigated . A number of further properties of the DHB ion and DHB ‐ILs with respect to potential applications in the field of hypergolic ILs have been studied experimentally or by theoretical methods …”
Section: Cyanohydridoborateskt[bhn(cn)4–n] (N = 1–3)mentioning
confidence: 99%
“…prepared DHB ‐ILs from chloride‐ or bromide‐ILs and Ag[BH 2 (CN) 2 ] and tested these ILs as hypergolic fluids . The proton affinity of selected anions, including the DHB anion,, and proton transfer energies from organic cations to these anions in energetic ILs were investigated . A number of further properties of the DHB ion and DHB ‐ILs with respect to potential applications in the field of hypergolic ILs have been studied experimentally or by theoretical methods …”
Section: Cyanohydridoborateskt[bhn(cn)4–n] (N = 1–3)mentioning
confidence: 99%
“…[148] Specifically,g uanidinium, dimethyltriazani-um, triethylammonium, N-ethyl-N-methylpyrrolidinium, N-ethylpyridinium, 1,4-dimethyl-1,2,4-triazolium, 1-ethyl-4-methyl-1,2,4-triazolium, and 1-butyl-4-methyl-1,2,4-triazoliumc ations were studied. To estimate the cation impact,a na binitio study of cation protona ffinity and proton transfer energy was performed for as et of cations at the MP2 level of theory.…”
Section: Hypergolic Ilsmentioning
confidence: 99%
“…To estimate the cation impact,a na binitio study of cation protona ffinity and proton transfer energy was performed for as et of cations at the MP2 level of theory. [148] Specifically,g uanidinium, dimethyltriazani-um, triethylammonium, N-ethyl-N-methylpyrrolidinium, N-ethylpyridinium, 1,4-dimethyl-1,2,4-triazolium, 1-ethyl-4-methyl-1,2,4-triazolium, and 1-butyl-4-methyl-1,2,4-triazoliumc ations were studied. The proton-transfer energiesf rom the cations to as et of anions studied previously were calculated;a ni nverse correlation between the latter and the likelihood thatt he cation/anion combination will react hypergolically with WFNA was found.…”
Section: Hypergolic Ilsmentioning
confidence: 99%
“…6, the first chemical reaction (i.e., the reaction that occurred at the lowest temperature) for both ILs was the deprotonation of the phosphonium cation by the salicylate/benzoate anion. Proton-transfer reactions between the cation and anion have been previously reported in phosphonium-based ILs 96,97 and in other systems, including native-like protein ions, 98,99 hypergolic fuels ILs, 100 and amino acid 101 ILs. It was also reported that the energy barriers for proton-transfer reactions are much lower than other reactions in thermal decomposition of hydrocarbons.…”
Section: Themogravimetric Experimentsmentioning
confidence: 85%